Diarylethene‐Based Photoswitchable Inhibitors of Serine Proteases. Issue 40 (25th August 2021) - Babii, Oleg; Afonin, Sergii; Diel, Christian; Huhn, Marcel; Dommermuth, Jennifer; Schober, Tim; Koniev, Serhii; Hrebonkin, Andrii; Nesterov‐Mueller, Alexander; Komarov, Igor V.; Ulrich, Anne S.
Abstract: A bicyclic peptide scaffold was chemically adapted to generate diarylethene‐based photoswitchable inhibitors of serine protease Bos taurus trypsin 1 (T1). Starting from a prototype molecule—sunflower trypsin inhibitor‐1 (SFTI‐1 )—we obtained light‐controllable inhibitors of T1 with Ki in the low nanomolar range, whose activity could be modulated over 20‐fold by irradiation. The inhibitory potency as well as resistance to proteolytic degradation were systematically studied on a series of 17 SFTI‐1 analogues. The hydrogen bond network that stabilizes the structure of inhibitors and possibly the enzyme–inhibitor binding dynamics were affected by isomerization of the photoswitch. The feasibility of manipulating enzyme activity in time and space was demonstrated by controlled digestion of gelatin‐based hydrogel and an antimicrobial peptide BP100‐RW. Finally, our design principles of diarylethene photoswitches are shown to apply also for the development of other serine protease inhibitors. Abstract : Bicyclic diarylethene‐containing analogues of the sunflower trypsin inhibitor‐1 (SFTI‐1 ) can modulate activity of serine proteases in the nanomolar–micromolar range in highly efficient photocontrollable manner.